K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 5 2019

\(2\cdot\left|\frac{1}{2}\cdot x-\frac{1}{3}\right|-\frac{3}{2}=\frac{1}{4}\)

\(=>2\cdot\left|\frac{1}{2}\cdot x-\frac{1}{3}\right|=\frac{1}{4}+\frac{3}{2}=\frac{7}{4}\)

\(=>\left|\frac{1}{2}\cdot x-\frac{1}{3}\right|=\frac{7}{4}:2=\frac{7}{8}\)

\(=>\frac{1}{2}\cdot x-\frac{1}{3}=\text{±}\frac{7}{8}\)

\(+\frac{1}{2}\cdot x-\frac{1}{3}=\frac{7}{8}\)

\(=>\frac{1}{2}x=\frac{7}{8}+\frac{1}{3}=\frac{29}{24}\)

\(=>x=\frac{29}{24}:\frac{1}{2}=\frac{29}{12}\)

\(+\frac{1}{2}\cdot x-\frac{1}{3}=-\frac{7}{8}\)

\(=>\frac{1}{2}\cdot x=-\frac{7}{8}+\frac{1}{3}=-\frac{13}{24}\)

\(=>x=-\frac{13}{24}:\frac{1}{20}=-\frac{13}{12}\)

14 tháng 5 2019

\(2.\left|\frac{1}{2}x-\frac{1}{3}\right|-\frac{3}{2}=\frac{1}{4}\)

\(2.\left|\frac{1}{2}x-\frac{1}{3}\right|=\frac{1}{4}+\frac{3}{2}\)

\(2.\left|\frac{1}{2}x-\frac{1}{3}\right|=\frac{7}{4}\)

\(\left|\frac{1}{2}x-\frac{1}{3}\right|=\frac{7}{4}:2\)

\(\left|\frac{1}{2}x-\frac{1}{3}\right|=\frac{7}{8}\)

\(\Rightarrow\orbr{\begin{cases}\frac{1}{2}x-\frac{1}{3}=\frac{7}{8}\\\frac{1}{2}x-\frac{1}{3}=\frac{-7}{8}\end{cases}}\Rightarrow\orbr{\begin{cases}\frac{1}{2}x=\frac{7}{8}+\frac{1}{3}\\\frac{1}{2}x=\frac{-7}{8}+\frac{1}{3}\end{cases}\Rightarrow\orbr{\begin{cases}\frac{1}{2}x=\frac{29}{24}\\\frac{1}{2}x=\frac{-13}{24}\end{cases}}}\)

\(\Rightarrow\orbr{\begin{cases}x=\frac{29}{24}:\frac{1}{2}\\x=\frac{-13}{24}:\frac{1}{2}\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{29}{12}\\x=\frac{-13}{12}\end{cases}}}\)

Vậy .....................................

~ Hok tốt ~

26 tháng 3 2019

\(x\div4\frac{1}{3}=-2,5\)

\(\Leftrightarrow x\div\frac{13}{3}=\frac{-5}{2}\)

\(\Leftrightarrow x=\frac{-5}{2}.\frac{13}{3}\)

\(\Leftrightarrow x=\frac{-65}{6}\)

\(x\div\frac{-3}{5}=\frac{-10}{21}\)

\(\Leftrightarrow x=\frac{-10}{21}.\frac{-3}{5}\)

\(\Leftrightarrow x=\frac{30}{105}\)

\(\Leftrightarrow x=\frac{2}{7}\)

26 tháng 3 2019

\(\frac{2}{3}x-\frac{1}{2}=\frac{1}{10}\)

\(\Leftrightarrow\frac{2}{3}x=\frac{1}{10}+\frac{1}{2}\)

\(\Leftrightarrow\frac{2}{3}x=\frac{6}{10}\)

\(\Leftrightarrow x=\frac{6}{10}\div\frac{2}{3}\)

\(\Leftrightarrow x=\frac{18}{20}\)

\(\Leftrightarrow x=\frac{9}{10}\)

\(\frac{1}{2}x+\frac{1}{2}=\frac{5}{2}\)

\(\Leftrightarrow\frac{1}{2}\left(x+1\right)=\frac{5}{2}\)

\(\Leftrightarrow\left(x+1\right)=\frac{5}{2}\div\frac{1}{2}\)

\(\Leftrightarrow\left(x+1\right)=5\)

\(\Leftrightarrow x=5-1\)

\(\Leftrightarrow x=4\)

26 tháng 7 2020

\(\left(x-2\right):2.3=6\)

\(\Leftrightarrow\left(x-2\right):2=2\)

\(\Leftrightarrow\left(x-2\right)=4\)

\(\Leftrightarrow x=4+2=6\)

c) ta có

\(\left[\left(2x+1\right)+1\right]m:2=625\)

\(\Leftrightarrow\left[\left(2x+1\right)+1\right]\left\{\left[\left(2x+1\right)-1\right]:2+1\right\}=1250\)

\(\Leftrightarrow\left(2x+1\right)^2+1-1:2+1=1250\)

\(\Leftrightarrow\left(2x+1\right)^2+1-2+1=1250\)

\(\Leftrightarrow\left(2x+1\right)^2+1-2=1249\)

\(\Leftrightarrow\left(2x+1\right)^2+1=1251\)

\(\Leftrightarrow\left(2x+1\right)^2=1250\)

...

2

\(\left(x-\frac{1}{2}\right).\frac{5}{3}=\frac{7}{4}-\frac{1}{2}\)

\(\Leftrightarrow\left(x-\frac{1}{2}\right).\frac{5}{3}=\frac{5}{4}\)

\(\Leftrightarrow\left(x-\frac{1}{2}\right)=\frac{5}{4}:\frac{5}{3}\)

\(\Leftrightarrow\left(x-\frac{1}{2}\right)=\frac{5}{4}.\frac{3}{5}\)

\(\Leftrightarrow x-\frac{1}{2}=\frac{3}{4}\)

\(\Leftrightarrow x=\frac{3}{4}+\frac{1}{2}=\frac{5}{4}\)

7 tháng 4 2018

2 nha@ nhớ tk cho mình@  >_<

7 tháng 4 2018

\(2.\left|\frac{1}{2}x-\frac{1}{3}\right|-\frac{3}{2}=\frac{1}{4}\)

\(2.\left|\frac{1}{2}x-\frac{1}{3}\right|=\frac{7}{4}\)

\(\left|\frac{1}{2}x-\frac{1}{3}\right|=\frac{7}{8}\)

=> \(\orbr{\begin{cases}\frac{1}{2}x-\frac{1}{3}=\frac{7}{8}\\\frac{1}{2}x-\frac{1}{3}=\frac{-7}{8}\end{cases}}\)

=> \(\orbr{\begin{cases}\frac{1}{2}x=\frac{29}{24}\\\frac{1}{2}x=\frac{-13}{24}\end{cases}}\)

=> \(\orbr{\begin{cases}x=\frac{29}{12}\\x=\frac{-13}{12}\end{cases}}\)

Vậy \(x\in\left\{\frac{29}{12};\frac{-13}{12}\right\}\)

~~~

#Sunrise

18 tháng 7 2017

\(3.\)

\(\frac{x-1}{2011}+\frac{x-2}{2010}+\frac{x-3}{2009}=\frac{x-4}{2008}\)

\(\Rightarrow\)\(\frac{x-1}{2011}-1+\frac{x-2}{2010}-1+\frac{x-3}{2009}-1-\frac{x-4}{2008}+1+2=0\)

\(\Rightarrow\)\(\frac{x-1}{2011}-\frac{2011}{2011}+\frac{x-2}{2010}-\frac{2010}{2010}+\frac{x-3}{2009}-\frac{2009}{2009}-\frac{x-4}{2008}+\frac{2008}{2008}=0\)

\(\Rightarrow\)\(\frac{x-2012}{2011}+\frac{x-2012}{2010}+\frac{x-2012}{2009}-\frac{x-2012}{2008}=0\)

\(\Rightarrow\)\(x-2012\left(\frac{1}{2011}+\frac{1}{2010}+\frac{1}{2009}+\frac{1}{2008}\right)=0\)

\(\Rightarrow\)\(x=2012\)